Processing and characterization of waste leather based polycaprolactone biocomposites - Joseph, Seena; Ambone, Tushar S.; Salvekar, Abhijit V.; Jaisankar, S. N.; Saravanan, P.; Deenadayalan, E. (Polymer Composites, 2017)
Waste leather buff (WLB) filled polycaprolactone (PCL) composites were prepared by twin-screw extrusion varying the WLB content from 2% to 40%. These composites were extensively characterized by several techniques in order to establish micro and macroscopic properties. Addition of WLB resulted in improvement of tensile modulus of neat PCL and reduction in percentage crystallinity of PCL matrix was observed with increase in WLB content. Interfacial adhesion and dispersion of WLB on PCL matrix was investigated using Scanning Electron Microscope. Percentage of water uptake increased with increase in concentration of WLB in the composite. These biodegradable composites could be used to develop low cost materials suitable for applications in footwear industry, for making bags, suitcases, etc., eliminating the environmental issues arising from WLB generated from tanneries in leather industry. POLYM. COMPOS., 38:2889-2897, 2017. (c) 2015 Society of Plastics Engineers

Tuning controlled release behavior of starch granules using nanofibrillated cellulose derived from waste sugarcane bagasse - Patil, Mayur D.; Patil, Vishal D.; Sapre, Aditya A.; Ambone, Tushar S.; Torris, Arun A. T.; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (ACS Sustainable Chemistry & Engineering, 2018)
Controlled release formulations help to encapsulate agrochemicals and deliver at a sustained rate. Growing environmental challenges have increased the need for controlled release systems based on sustainable feed-stocks. To this end, we report here the preparation and properties of a monolith-type controlled release granular formulation based on two ubiquitous biopolymers, starch and cellulose. Cellulose nanofibers (CNFs) derived from waste sugarcane bagasse were mixed with gelatinized maize starch and urea formaldehyde to yield nanocomposite granular formulation. Dimethyl phthalate (DMP) was used as model encapsulant. The morphology of CNFs and CNFreinforced starch granules was characterized by transmission electron microscopy, scanning electron microscopy, BET porosimetry, and X-ray tomography. Incorporation of only 2-4 wt % CNFs led to a significant reduction in porosity as compared to that for neat starch granules, while the water uptake was enhanced by 20-30%. Reinforcing starch with CNFs led to a significant reduction in initial release rate and yet higher overall release of DMP, thereby allowing effective utilization of entrapped chemicals. This interesting release behavior could be attributed to two competing factors, water uptake-induced diffusion and barrier effects rendered by nanocellulose network.